Evaluating tennis player performance based on different types of grip strength - Zhang, K.; Cui, J.; Jia, Y.; Wang, L. (BMC Sports Science, Medicine and Rehabilitation, 2026)
Grip strength is the concrete manifestation of the hand-wrist-forearm segment that links the body and the instrument at the end of the kinetic chain in events of handheld equipment. It plays a crucial role as a "gatekeeper" in transmission, control and coordination of force. A review of the literatures about the relationship between grip strength and tennis sports performance is provided to clarify the potential functions of grip strength within the kinetic chain, demonstrate more details of the performance of the hand-wrist-forearm segment in events of handheld implements, and enrich the theory of the kinetic chain. The "grip", "grip strength", "dynamic grip strength", "static grip strength", "grip endurance" and "tennis" as keywords are searched in internationally recognized databases (Web of Science, PubMed, Google Scholar, Scopus, and ProQuest, etc.). Relevant literatures are collected, screened, read, organized and analyzed. Here, grip strength is classified into specific and non-specific categories based on the differences in testing environment. By summarizing the functions of specific and non-specific grip strength, it is found that both kinds of grip strengths have significant intrinsic value. This review provides a new perspective for understanding the performance of the end of the kinetic chain and has great significance for enriching the theory of the kinetic chain.